Homozygous missense variant in BMPR1A resulting in BMPR signaling disruption and syndromic features. Issue 11 (7th September 2019) - Russell, Bianca E.; Rigueur, Diana; Weaver, Kathryn N.; Sund, Kristen; Basil, Janet S.; Hufnagel, Robert B.; Prows, Cynthia A.; Oestreich, Alan; Al‐Gazali, Lihadh; Hopkin, Robert J; Saal, Howard M.; Lyons, Karen; et al.
Abstract: Background: The bone morphogenetic protein (BMP) pathway is known to play an imperative role in bone, cartilage, and cardiac tissue formation. Truncating, heterozygous variants, and deletions of one of the essential receptors in this pathway, Bone Morphogenetic Protein Receptor Type1A ( BMPR1A ), have been associated with autosomal dominant juvenile polyposis. Heterozygous deletions have also been associated with cardiac and minor skeletal anomalies. Populations with atrioventricular septal defects are enriched for rare missense BMPR1A variants. Methods: We report on a patient with a homozygous missense variant in BMPR1A causing skeletal abnormalities, growth failure a large atrial septal defect, severe subglottic stenosis, laryngomalacia, facial dysmorphisms, and developmental delays. Results: Functional analysis of this variant shows increased chondrocyte death for cells with the mutated receptor, increased phosphorylated R‐Smads1/5/8, and loss of Sox9 expression mediated by decreased phosphorylation of p38. Conclusion: This homozygous missense variant in BMPR1A appears to cause a distinct clinical phenotype. Abstract : We report on a patient with a homozygous missense variant in BMPR1A causing skeletal abnormalities, growth failure a large atrial septal defect, severe subglottic stenosis, laryngomalacia, facial dysmorphisms, and developmental delays. Functional analysis of this variant shows increased chondrocyte death for cells with the mutated receptor and abnormal downstream signaling. This homozygous missense variant in BMPR1A appears to cause a distinct clinical phenotype.